2021
DOI: 10.1021/acs.cgd.1c00619
|View full text |Cite
|
Sign up to set email alerts
|

Synthon Polymorphism and π–π Stacking inN-Phenyl-2-hydroxynicotinanilides

Abstract: A lactam−lactam dimer (LLD) and lactam NH•••OC (amide) catemer (LAC) are two competing motifs in N-phenyl-2-hydroxynicotinanilides (PHNAs). Steric effects play an important role in determining the outcome of this competition, and in general, PHNAs with no or negligible steric hindrance take on a near-planar conformation and form LLDs, rather than the widely observed amide NH•••OC hydrogen-bond chains. Conversely, those with significant steric hindrance are forced to take on a twisted conformation and form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…A recent study suggested the role of the π-stacking contribution in generating independent types of synthons in each case, leading to synthon-polymorphs. 12 In the present case, it is the competition of the DMF molecule for the hydrogen bond with the urea moiety and the ability to adopt hydrogen-bonded dimer that were the key factors. The difference between the types of assemblies was that in one case, it had a sulfonamide⋯5-methyl-1,2-oxazole and urea⋯DMF synthons and in the other cases, urea⋯5-methyl-1,2-oxazole and DMF⋯amine synthons were present.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…A recent study suggested the role of the π-stacking contribution in generating independent types of synthons in each case, leading to synthon-polymorphs. 12 In the present case, it is the competition of the DMF molecule for the hydrogen bond with the urea moiety and the ability to adopt hydrogen-bonded dimer that were the key factors. The difference between the types of assemblies was that in one case, it had a sulfonamide⋯5-methyl-1,2-oxazole and urea⋯DMF synthons and in the other cases, urea⋯5-methyl-1,2-oxazole and DMF⋯amine synthons were present.…”
Section: Resultsmentioning
confidence: 79%
“…Synthon competition in certain two-component systems of such derivatives causes polymorphism. [12][13][14][15][16] Having several polymorphs of a compound presents diverse new properties, but sometimes this is disadvantageous. For example, special techniques are required to enhance the selectivity of a form 17 when there is a possibility of concomitant polymorphs in conventional crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…† Although we did not get the single crystal structure of anhydrate-III, we think that its structure should be like that of anhydrate-I, which is filled with abundant π⋯π interactions, and both have high packing efficiency; thus, anhydrate-III exhibits a high melting point and extremely weak hygroscopicity. [81][82][83][84]…”
Section: Thermal Stability Analysismentioning
confidence: 99%
“…Besides, extensive studies of the influence of hydrogen bonding on the isomeric state of acylaminopyridines were performed by Ośmiałowski et al [ 21 , 22 , 23 , 24 , 25 , 26 ]. In addition, phthalic acids and lactams are interesting in terms of conformational changes [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. These compounds contain two carboxyl groups not coupled together and, therefore, the steric repulsion can induce significant conformational changes.…”
Section: Introductionmentioning
confidence: 99%